STRES DAN MOTIVASI BELAJAR DARING PADA SISWA KELAS VIII DI SMPN 2 CURUG TANGERANG TAHUN 2021 - Winarni, Lastri Mei; Gunawan, Endra; Perdiana, Riska (Nusantara Hasana Journal, 2022)
Online Learning (On the Network) or online learning activities carried out during the current pandemic, therefore there are quite a lot of advantages and disadvantages that can be felt by students and can trigger stress and be accompanied by learning motivation. Research objectives of this study was to identify the relationship between stress and online learning motivation in class VIII students at SMPN 2 Curug. This study uses a descriptive correlative research design to determine the level of stress and motivation to learn online in class VIII students at SMPN 2 Curug. The population in this study were active students of class VIII totaling 132 students at SMPN 2 Curug . There is a relationship between stress and online learning motivation in class VIII students.